Development Of Zirconia Nanotubes And Iron Oxide Nanopores By Anodization Method For Photoactive Material - Rozana, Monna (2018)
Solar energy can be utilized for electricity generation and water purification. To capture solar photons, photoactive materials are required. However, several problems were identified on the use of oxide as photoactive material: (1) recombination of photogenerated electron-hole pairs, (2) visible light utilization and (3) amorphous oxide limits the application. In this thesis, ZrO2 nanotubes (ZNTs), α–Fe2O3 nanopores (FNPs) and α–Fe2O3 nanotubes (FNTs) were successfully fabricated by anodization in ammonium flouride (NH4F)/ethylene glycol (EG) electrolyte containing various O2–and/or OH–providers (H2O, KOH, LiOH or H2O2) to overcome the mentioned problems. The ZNTs, FNPs and FNTs were used as photoanode in a photoelectrochemical cell to generate photocurrent and as photocatalyst to degrade methyl orange (MO). Double layered ZNTs with top layer tube diameter of 45 nm and larger nanotubes (140 nm) at bottom layer were obtained in KOH/NH4F/EG. 7.4 µm length ZNTs was formed in LiOH/NH4F/EG, however the surface was covered by anion/cation contamination (OH–, F–, CO32–, NH4+, and Li+). Meanwhile freestanding ZNTs (FS-ZNTs) were fabricated in H2O2/NH4F/EG due to oxygen evolution which aids in weakening the adherence of the ZNTs from Zr. As-anodized ZNTs formed in LiOH/NH4F/EG have tetragonal ZrO2 crystallite due to the existence of oxygen vacancies, OH–and impurities. After annealing, ZNTs have majority monoclinic ZrO2 whereas FS-ZNTs have majority tetragonal ZrO2 with bandgap of ~5 eV. FS-ZNTs exhibited 34% MO degradation after 2 h of UV light whereas 9.5% MO degradation was observed after 2 h of visible light exposure. These indicate ZNTs can be activated under visible light to degrade MO. LiOH derived ZNTs with good adherence with Zr generated high photocurrent of 2.18 mA cm–2at 1 VAg/AgCl under UV, but under visible light very small current of 1.69 x 10–4 mA cm–2at 1 VAg/AgCl were generated. ZNTs may not suitable to be used as photoanode in a PEC cell under visible light despite the band narrowing due to defects within their energy gap. A smaller bandgap material α–Fe2O3 was fabricated by anodization of iron (Fe) in an attempt to produce visible light activated material. Anodization of Fe in H2O, KOH, or LiOH/NH4F/EG produced FNPs. The as-anodized FNPs formed in KOH or LiOH electrolyte have crystalline FeOOH due to the high content of OH–. FNTs with grassy surface were formed in H2O2/NH4F/EG. After annealing, FNPs/FNTs have majority α–Fe2O3 phase. FNPs formed in H2O/NH4F/EG generated highest photocurrent of 25.6 mA cm–2at 1 VAg/AgCl due to the presence of –Fe2O3 and thin interfacial layer. The lowest photocurrent of 2.8 mA cm–2at 1 VAg/AgCl was produced from FNTs. The reduced photocurrent may be due the morphologies and the existence of Fe3O4. Annealing must be done in nitrogen to reduce the growth of Fe3O4. As for the MO degradation, LiOH derived FNPs exhibited 34% degradation after 2 h of visible light exposure. The sample has bandgap energy of 2.2 eV and defect state at 1.9 eV due to oxygen vacancies resulted in increasing free holes density, hence enhanced MO degradation.